Sinus floor augmentation with autogenous bone vs. a bovine‐derived xenograft – a 5‐year retrospective study. Issue 6 (20th February 2014) - Lutz, Rainer; Berger‐Fink, Susanne; Stockmann, Philipp; Neukam, Friedrich Wilhelm; Schlegel, Karl Andreas
Abstract: Objectives: The long‐term outcome after sinus augmentation with autogenous bone or a bovine xenograft (Bio‐Oss ® ) was assessed in 47 patients. Inclusion criterion was a vertical dimension of the maxilla of <4 mm. After a functional loading period of 60 months, implant survival and reduction in the augmentation height were compared between the two groups evaluated. Material and methods: Sinus augmentation was performed using mandibular bone grafts or Bio‐Oss ® . In the autogenous bone group, 70 implants were placed in 23 patients, while in the Bio‐Oss ® group, 24 patients received 98 implants. Fisher's exact test and equivalence testing were used to compare implant survival rates. Results: The overall survival rate of the implants was 95.8% 5 years after implant insertion. In the autogenous bone group, the implants had a survival rate of 97.1%, while in the Bio‐Oss ® group, 94.9% of the implants survived. The difference was not statistically significant ( P  > 0.05); both treatments are equivalent (confidence interval 90%) for the equivalence interval [−0.1; 0.1]. 43.5% of the cases showed no reduction in the augmentation height 5 years after implant insertion, when augmentation was performed with autogenous bone, while in the Bio‐Oss ® group, no resorption was found in 50% of the augmented areas. Up to 25% reduction in augmentation height was found in 47.8% in the autogenous and in 45.8% in the Bio‐Oss ® group. In 8.7% of all cases in the autogenous bone group and in 4.2 % in the Bio‐Oss ® group, up to 50% of the augmented height was resorbed. Conclusion: After a 5 years evaluation period, Bio‐Oss ® as material for the indication maxillary sinus augmentation shows to be equivalent to autogenous bone grafting.